Recent advances in the science and technology of natural zeolites in Iran. (24th May 2019) - Behin, Jamshid; Ghadamnan, Elmira; Kazemian, Hossein
Abstract: Iran has significant deposits of high-purity natural zeolites. Many Iranian scholars conduct scientific research on porous materials, from natural and synthetic zeolites to metal organic framework materials. Iranian zeolite deposits and associated research are reviewed here. Various industrial applications of natural zeolites, from agriculture to animal husbandry to the construction industry and beyond are discussed here.